The accuracy of polyp assessment during colonoscopy in FIT-screening is not acceptable on a routine basis - Stegeman, Inge; van Doorn, Sascha; Mallant-Hent, Rosalie; van der Vlugt, Manon; Mundt, Marco; Fockens, Paul; Bossuyt, Patrick; Dekker, Evelien (Endoscopy International Open, 2014)
Background: During colonoscopy, correct assessment of polyps is important. Recognition of early carcinomas is needed for tailor-made treatment and avoidance of unnecessary complications. Moreover, accurate diagnosis of diminutive lesions could result in a safe resect and discard strategy. We assessed the accuracy of polyp assessment by general endoscopists without specific training or experience in image-enhanced endoscopy during routine colonoscopies within a fecal immunochemical test (FIT)-based screening program.Methods: Data were collected in the third round of a FIT-based colorectal cancer screening pilot program. Patients diagnosed as FIT-positive (318) underwent colonoscopy using Olympus (160 and 180 series) endoscopes without magnification or routine use of (virtual) chromoendoscopy. Endoscopists received no special training. They made an on-site evaluation and classified detected polyps as hyperplastic, adenoma, carcinoma. Samples of resected lesions were sent for histopathology. Sensitivity and specificity were calculated. We differentiated for fellows and consultants.Results: In the 318 patients with a positive FIT-screening result, 683 lesions were detected; 564 lesions were included in the analyses. The pathologist classified these lesions as 141 hyperplastic polyps, 349 adenomas, 16 carcinomas, and 58 other. Sensitivity for diagnosis of adenomas was 88 % (95 %CI 84 – 91); specificity 49 % (95 %CI 42 – 55). Of the 16 colorectal carcinomas, endoscopists diagnosed four incorrectly (sensitivity 75 % [95 %CI 44 – 89]; specificity 99 % [95 %CI 98 – 100]), including three stage I cancers and one stage III cancer. There were no differences in accuracy of diagnosis that related to different sizes of lesions or the experience of the endoscopist.Conclusion: In a routine FIT-based screening setting and without specific training or routine use of (digital) chromoendoscopy, endoscopic prediction of the histopathology of colonic lesions is inaccurate when the procedure is performed by general endoscopists.